A comprehensive analysis on the ecosystem services of Elaeocarpus L. (Elaeocarpaceae): a review - Sharma, Sheenu; Hussain, Sabir; Rai, Durg Vijay; Singh, Anand Narain (Journal of Phytology, 2023)
The Elaeocarpus is considered the largest genus in the family Elaeocarpaceae. It is commonly called ‘Rudraksha’ in India and has a noteworthy attachment with the Indians, mostly Hindus. The plant is known for its beneficial aspects and supply of various ecosystem services, particularly in medicinal sciences. The present study provides a comprehensive review of the genus Elaeocarpus for its ecosystem services in the context of human wellbeing. A literature survey was conducted from 1970 to 2020 on internet scientific databases such as Scopus, Science Direct, Google Scholar, PubMed, and Web of Science using strings such as, Elaeocarpus, Rudraksha, medicine, conservation, tradition, and services. One hundred two publications were considered for data extraction and finalising the review. Firstly, we classified the ecosystem services under respective classes as provided by MEA (2005), and the remaining benefits that didn’t fit under the classification were presented separately. It has been reported that Rudraksha delivers all categories of ecosystem services: provisioning, regulating, cultural, and supporting services. In addition, the Rudraksha plant owes a high status in medicinal science, ayurveda, and religious mythology. In the last five decades, studies were conducted on various species of Elaeocarpus for their beneficial aspects. It was found that Elaeocarpus plants have a vital role in ayurveda, pharmaceuticals, and pharmacological and astrological science. In addition, they have been used as food, firewood, timber, and the production of secondary metabolites and their role in cultural and religious dimensions are very clearly discussed. The provisioning and cultural services delivered by Rudraksha constitute only 30% and 10% of the services mentioned in MEA (2005). However, only a little research has been conducted on regulatory and supporting services provided by Rudraksha. Therefore, for a long-term sustainability and multifunctionality assessment, the extension of ecosystem services regarding individual plant’s (tree) services should be highly recommended. Hence, the present review investigates the scientific knowledge about the ecosystem services of the Elaeocarpus.